Digital Leadership Dosen dan AI Literacy Mahasiswa: Studi pada Program Studi Manajemen Pendidikan Islam - Huwaidah, Nabila; Yoenanto, Nono Hery; Fajruddin, Muhammad Nabhan; Fauziana, Sartika Putri (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2026)
This study examines the impact of lecturers’ digital leadership on students’ AI literacy in the context of the growing use of digital technology and Artificial Intelligence (AI) in higher education. Despite high levels of technological exposure, students do not always demonstrate critical and productive usage skills. Therefore, this research aims to analyze how digital leadership influences students’ AI literacy. A quantitative approach with a survey design was employed, involving 102 students selected through purposive sampling. Data were collected using Likert-scale questionnaires, where digital leadership was measured using the Digital Leadership Scale and AI literacy was assessed using the Meta AI Literacy Scale (MAILS). Data analysis was conducted using simple linear regression. The results indicate that lecturers’ digital leadership has a positive and significant effect on students’ AI literacy (β = 0.550, p < 0.001), contributing 30.3% to the variance. These findings suggest that lecturers, as leaders in digital-based learning, play a crucial role in enhancing students’ ability to understand and effectively utilize AI. Additionally, descriptive results reveal that although students perceive lecturers’ digital leadership as high, their level of AI literacy remains moderate, indicating a gap between technological exposure and actual competence. Practically, the findings underscore the importance of strengthening lecturers’ digital leadership through the development of digital competencies and the integration of technology in learning, including within religious higher education contexts that also emphasize ethical considerations in AI use.